Homestasis Model Assessment–Adiponectin ratio and Adiponectin –Resistin index as markers of insulin resistance in type 2diabetes mellitus - Khalid Hameed, Ikhlas; Rashid, Nada F.; Abed, Baydaa A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Insulin resistance (IR) is an important clinical and biochemical determinant of diabetes and many other clinical states. The gold standard method for IR estimation is the hyperinsulinemic euglycaemic glucose clamp. Adiponectin and resistin are adipocytes derived hormones that play important role in the regulation of glucose, fat metabolism and insulin resistance. Objective: this study aimed to assess the validity of Homestasis Model Assessment–Adiponectin ratio and Adiponectin –Resistin index as markers of insulin resistance in type 2 diabetic mellitus (T2DM) patients. Design: Ninety (T2DM) overweight male subjects were enrolled in this cross sectional study, detailed history, physical examination and anthropometric measures including BMI, waist, and hip circumference were done to all the participants. Fasting serum samples were obtained and used for the measurement of serum glucose, serum triglyceride, high density lipoprotein(HDL),very low density lipoprotein(VLDL),HbA1c ,also serum insulin, adiponectin ,resistin were measured and HOMA-IR, HOMA-AD and AR-index were calculated.SPSS-17 was used to analyze the data. Results: AR-index correlates significantly with FSG, Fasting Insulin and HOMA-IR (r =0.534.p=0.005), (r=0.545, p=0.005), (r=0.506, p=0.008) respectively HOMA-AD correlates with FSG (R=0.551, P=0.001), insulin (P=0.956,p=0.000),HOMA-IR(r =0.952, p=0.000). AUC for AR-index (0.800) and for HOMA-AD (0.905). Conclusions: HOMA-AD and AR-index are reliable and valid measures for the assessment of insulin resistance in type 2 diabetic patients.